Service Orienting BPM service-oriented process management. - Kulkarni, Neeraj (SOA webservices journal.)
Business process management (BPM) is a business management philosophy consisting of the idea that a business can be understood and managed solely in terms of business processes. BPM is process-centric and responsive to change in business requirements and objectives. Businesses are defined through dynamic processes that change almost constantly.